Older adults' use of social media in communicating with their immediate family members - Olaivar, Bea Katrina C.; Rosario, Patricia M. (College of Home Economics, University of the Philippines Diliman, 2019)
This study aims to explore the experiences of older adults in using social media to communicate with their immediate family members. It focuses on their circumstances of use, themes of communication between them and their immediate family members online, their perceived advantages of using social media, and the barriers they encounter while using it. Through purposive and snowball sampling, 30 older adults from Metro Manila were selected to participate in an in-depth interview exhaustive of their experiences on and understanding of social media. Data gathered from the interviews are subjected to the process of thematic analysis wherein codes are generated through the identification of themes and subthemes. The results from the data are also cross-referenced with the Psychosocial Theory and Activity Theory. Results show that older adults address their inherent need to communicate as they engage in pangangamusta and paghahabilin with their immediate family members on social media. Doing so lets them exhibit concern and care for their families and further their own development and well-being through their social relationships. This allows them to find social media useful, even if this comes with external and developmental barriers brought about by their circumstances as older adults. Despite this, results also display how older adults feel that, compared to younger generations, they are not as in tune with using social media, such that they must work towards adapting to its existing form.